Revision of Diphaulacosoma Jacoby, an endemic flea beetle genus from Madagascar, with description of three new species (Coleoptera: Chrysomelidae, Galerucinae, Alticini) - Biondi, Maurizio; D'Alessandro, Paola (Fragmenta entomologica, 2016)
A taxonomic revision of the flea beetle genus Diphaulacosoma Jacoby, endemic to Madagascar, is provided. This genus includes seven species of which three are new to science: D. elegans sp. n., D. jenisi sp. n., and D. nigroscutis sp. n. An updated catalogue including new material, new faunistic records, distributions, chorotypes, and ecological notes is supplied. Lectotypes for Diphaulacosoma laevipenne Jacoby, D. bicolor (Weise) and D. scutellare (Weise) are designated. Additionally, the revision comprises a key for the identification of all seven species considered, habitus photos, and microscope and scanning electron micrographs of diagnostic characters, including aedeagus and spermatheca.